Ion Pair Association Constant of Bis-1-Amidino-O-methylurea Copper(II) Acetate in Aqueous Medium at Different Temperature: A Conductance Study - Bag, Gopal Chandra; Singh, Th. David; Singh, N. Mohondas; Singh, N. Rajmuhon (Asian Journal of Chemistry, 2010)
Conductances of the bis-1-amidino-O-methylurea copper(II) acetate has been measured in aqueous medium at 278.15 to 313.15 K. The conductance data in all the cases have been analyzed by Shedlovsky equation to obtain Λo and KA value for the electrolyte. The effect of temperature on the Stokes’ radius for the complex cation has been discussed in the light of Walden product. Based on the KA values and temperature dependence of Λo the thermodynamic parameters have been determined. The results have been discussed in terms of ion-ion and ion-solvent interactions.